The Role of Learning Support and Chat-Sessions in Guided Internet-Based Cognitive Behavioral Therapy for Adolescents With Anxiety: A Factorial Design Study - Berg, Matilda; Rozental, Alexander; de Brun Mangs, Josefine; Näsman, Maja; Strömberg, Karin; Viberg, Linn; Wallner, Erik; Åhman, Hanna; Silfvernagel, Kristin; Zetterqvist, Maria; Topooco, Naira; Capusan, Andrea; et al. (Frontiers in Psychiatry, 2020)
Background Increased awareness of anxiety in adolescents emphasises the need for effective interventions. Internet-based cognitive behavioural therapy (ICBT) could be a resource-effective and evidence-based treatment option, but little is known about how to optimize ICBT or which factors boost outcomes. Recently, the role of knowledge in psychotherapy has received increased focus. Further, chat-sessions are of interest when trying to optimize ICBT for youths. This study aimed to evaluate the role of learning support and chat-sessions during ICBT for adolescent anxiety, using a factorial design. Method A total of 120 adolescents were randomised to one of four treatment groups, in a 2x2 design with two factors: with or without learning support and/or chat-sessions. Results Anxiety and depressive symptoms were reduced (Beck Anxiety Inventory- BAI; Cohen’s d =0.72; Beck Depression Inventory- BDI; d =0.97). There was a main effect of learning support on BAI (d =0.38), and learning support increased knowledge gain (d =0.42). There were no main effects or interactions related to the chat-sessions. Treatment effects were maintained at 6-months, but the added effect of learning support had by then vanished. Conclusion ICBT can be an effective alternative when treating adolescents with anxiety. Learning support could be of importance to enhance short-term treatment effects, and should be investigated further.